LAKHON PHANTHANG: IN BETWEEN TRADITIONAL THEATRE AND EDUCATIONAL SYSTEM IN THAILAND - Phakamas Jirajarupat (Proceeding IICACS, 2019)
In the past, lakhon phanthang emerges as a commercial theatre in Siam in the nineteenth century however at present it is named as a Thai traditional theatre. Under the Thai traditional theatre label, lakhon phanthang has been selected to present on the various Thai dance curricular in Thailand in order to preserving and developing the traditional dance-drama form. This paper examines the transmission of lakhon phanthang to the young generations through the dance educational system in Thailand by focusing on the existing of lakhon phanthang at three universities; 1) Bunditpatanasilpa Institute 2) Suan Sunandha Rajabhat University and 3) Chulalongkorn University, which are the prominent institutions in providing traditional dance and theatre education in Thailand. The finding represents the reflection of the role of educational institutions in the codification of performance. The process of learning and teaching lakhon phanthang are proposed as a set routine rather than a creative opportunity. Dance and theatre education in today’s educational system does not encourage the development of traditional forms but is seen primarily as a means of preserving them.Keywords: Lakhon phanthang, Thai dance eductation, Thai traditional theatre